Determining the Acceleration Due to Gravity Using a Smartphone-Based Pendulum System - Edison L. Uy; Ma. Noreen R. Eredia; John Lawrence A. Verzosa; Katrina M. Cabanacan; Rezy V. Mendaño; Carmen R. Lim (Scientia Publica Media, 2026)
This study aimed to find the acceleration due to gravity using a smartphone pendulum system with the Phyphox application. As the need for new ideas and real-world applications in science education increases, researchers have explored how mobile sensor technology can provide a more precise and user-friendly alternative to traditional stopwatch methods. A simple pendulum setup, consisting of a smartphone, a string, and a fixed support, was used to record oscillation periods at different lengths. Data were analyzed by plotting the square of the time period against the length of the pendulum, which allowed for the calculation of local gravitational acceleration through linear regression. The computed value of acceleration due to gravity was 8.86 m/s², differing by 9.41 percent from the accepted standard value of 9.81 m/s². This difference falls within an acceptable range for classroom experimentation, considering potential error sources such as air resistance, timing delays, and misalignment. The study aimed to achieve four main objectives: to collect data from different pendulum lengths, to calculate local gravity, to compare the results with the standard value, and to verify the accuracy of the experiments. The findings indicate that smartphones can successfully reinforce physics concepts and support hands-on, inquiry-based learning. Using mobile apps boosts engagement, curiosity, and essential skills for the twenty-first century. As schools seek affordable ways to teach laboratory concepts, mobile sensor technologies like Phyphox provide a practical and accessible solution, particularly for classrooms lacking traditional lab equipment.